2018
DOI: 10.1002/cav.1800
|View full text |Cite
|
Sign up to set email alerts
|

An intelligent, adaptive, performance‐sensitive, and virtual reality‐based gaming platform for the upper limb

Abstract: Stroke is a leading cause of adult disability, characterized by a spectrum of muscle weakness and movement abnormalities related to the upper limb. About 80% of individuals who had a stroke suffer from upper limb dysfunction. Conventional rehabilitation aims to improve one's ability to use paralyzed limbs through repetitive exercise under one‐on‐one supervision by physiotherapists. This poses difficulty given the limited availability of healthcare resources and the high cost of availing specialized services at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 44 publications
0
11
0
Order By: Relevance
“…This novel, multimodal and performance-sensitive exercise platform was experimented on 10 chronic stroke (>6 months) patients on unilateral shoulder abduction and adduction that are essential for the performance of daily living activities. The device resulted in greater accuracy and precision in hand activities and shoulder movements in stroke (p<0.05) [30,31].…”
Section: (Iii) Virtual Reality/haptics In Stroke Rehabilitationmentioning
confidence: 98%
See 1 more Smart Citation
“…This novel, multimodal and performance-sensitive exercise platform was experimented on 10 chronic stroke (>6 months) patients on unilateral shoulder abduction and adduction that are essential for the performance of daily living activities. The device resulted in greater accuracy and precision in hand activities and shoulder movements in stroke (p<0.05) [30,31].…”
Section: (Iii) Virtual Reality/haptics In Stroke Rehabilitationmentioning
confidence: 98%
“…fMRI and DTI have been a boon to understand the functional and structural recovery post stroke. The experience and environment rich plasticity has been well elucidated in research trials [8,9,31]. In another interesting research, we conducted fMRI analysis trial on functional imaging and effects of physiotherapy on diffusion tensor imaging at baseline, pre and post physiotherapy (8 weeks).…”
Section: Fmri and Stroke Recoverymentioning
confidence: 99%
“…In terms of exploration in the field of home medical devices, Dhiman et al considered the utilization of VR technology in the design of home medical devices on the basis of finding that stroke causes adult disability, to research and design a novel, multimodal, VR-based, and performance-sensitive rehabilitation training platform. A low-cost, family-oriented, and personalized medical rehabilitation platform was created, which made an important contribution to the development of the medical industry [11]. In the field of classroom education and teaching, Lamb et al studied the emerging teaching methods based on the implementation of the Next Generation Science Standard (NGSS).…”
Section: Foreign Researchesmentioning
confidence: 99%
“…From the perspective of personalization, some researchers allow game players to choose roles, scenes or personalized cognitive training tasks according to their own preferences to achieve personalized game design (Reategui et al, 2006 ; Wei, 2009 ; Hollingdale and Greitemeyer, 2013 ; Lin et al, 2013 ; Li et al, 2016 ; Nagle et al, 2016 ; Orji et al, 2017 ; Orji and Moffatt, 2018 ; Soares et al, 2018 ; Waltemate et al, 2018 ; Zibrek et al, 2018 ; González et al, 2019 ; Knutas et al, 2019 ; Troussas et al, 2019 ). There are also some researchers from the adaptive point of view, by dynamically changing the parameters in the game, automatically adapting to the player's game difficulty, dynamically generating new content and other methods to achieve the adaptive design of the game (Carro et al, 2002 ; Hunicke, 2005 ; Togelius et al, 2010 ; Johnson et al, 2014 ; Li et al, 2014 ; Yannakakis and Togelius, 2015 ; Shaker et al, 2016 ; Schadenberg et al, 2017 ; Soler-Dominguez et al, 2017 ; Ashish et al, 2018 ; Lopes et al, 2018 ; Shi and Chen, 2018 ; Souza et al, 2018 ; Denisova and Cairns, 2019 ; Dey et al, 2019 ; Hendrix et al, 2019 ; Liang et al, 2019 ; Pan et al, 2019 ; Papadimitriou et al, 2019 ; Peng et al, 2019 ; Plass et al, 2019 ; Sepulveda et al, 2019 ). Relevant research showed that adding personalized design to electronic science games for improving cognitive abilities could enhance the cognitive training experience of gamers, stimulate their interest in cognitive training, and better enhance the training experience and cognition ability of gamers (Reategui et al, 2006 ; Wei, 2009 ; Hollingdale and Greitemeyer, 2013 ; Lin et al, 2013 ; Li et al, 2016 ; Nagle et al, 2016 ; Orji et al, 2017 ; Orji and Moffatt, 2018 ; Soares et al, 2018 ; Waltemate et al, 2018 ; Zibrek et al, 2018 ; González et al,…”
Section: Introductionmentioning
confidence: 99%
“…There are also some researchers from the adaptive point of view, by dynamically changing the parameters in the game, automatically adapting to the player's game difficulty, dynamically generating new content and other methods to achieve the adaptive design of the game (Carro et al, 2002 ; Hunicke, 2005 ; Togelius et al, 2010 ; Johnson et al, 2014 ; Li et al, 2014 ; Yannakakis and Togelius, 2015 ; Shaker et al, 2016 ; Schadenberg et al, 2017 ; Soler-Dominguez et al, 2017 ; Ashish et al, 2018 ; Lopes et al, 2018 ; Shi and Chen, 2018 ; Souza et al, 2018 ; Denisova and Cairns, 2019 ; Dey et al, 2019 ; Hendrix et al, 2019 ; Liang et al, 2019 ; Pan et al, 2019 ; Papadimitriou et al, 2019 ; Peng et al, 2019 ; Plass et al, 2019 ; Sepulveda et al, 2019 ). Relevant research showed that adding personalized design to electronic science games for improving cognitive abilities could enhance the cognitive training experience of gamers, stimulate their interest in cognitive training, and better enhance the training experience and cognition ability of gamers (Reategui et al, 2006 ; Wei, 2009 ; Hollingdale and Greitemeyer, 2013 ; Lin et al, 2013 ; Li et al, 2016 ; Nagle et al, 2016 ; Orji et al, 2017 ; Orji and Moffatt, 2018 ; Soares et al, 2018 ; Waltemate et al, 2018 ; Zibrek et al, 2018 ; González et al, 2019 ; Knutas et al, 2019 ; Troussas et al, 2019 ); adding adaptive design to electronic science games used to improve cognitive ability, which can match the player's level with the difficulty of the game, so that gamers can obtain the best training effect (Carro et al, 2002 ; Hunicke, 2005 ; Togelius et al, 2010 ; Johnson et al, 2014 ; Li et al, 2014 ; Yannakakis and Togelius, 2015 ; Shaker et al, 2016 ; Schadenberg et al, 2017 ; Soler-Dominguez et al, 2017 ; Ashish et al, 2018 ; Lopes et al, 2018 ; Shi and Chen,…”
Section: Introductionmentioning
confidence: 99%